2022
DOI: 10.1021/acs.nanolett.2c03140
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Spectrally Resolved Single-Molecule Localization Microscopy at High Emitter Densities

Abstract: Single-molecule localization microscopy (SMLM) is a powerful super-resolution technique for elucidating structure and dynamics in the life-and material sciences. Simultaneously acquiring spectral information (spectrally resolved SMLM, sSMLM) has been hampered by several challenges: an increased complexity of the optical detection pathway, lower accessible emitter densities, and compromised spatio-spectral resolution.Here we present a single-component, low-cost implementation of sSMLM that addresses these chall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…Rather than measuring the photoluminescence of selected QDs one by one, we use MPS to measure emission spectra of typically 20–100 QDs simultaneously. The method is inspired by a recent study of QD blinking at the multiparticle level and slitless strategies that have previously been applied in the fields of bioimaging and astrophysics. In MPS (Figure a), QDs are sparsely distributed on a glass substrate and excited by wide-field illumination. Without the use of an entrance slit, the emission from these QDs is directed to our spectrometer that is equipped with a reflective diffraction grating.…”
Section: Resultsmentioning
confidence: 99%
“…Rather than measuring the photoluminescence of selected QDs one by one, we use MPS to measure emission spectra of typically 20–100 QDs simultaneously. The method is inspired by a recent study of QD blinking at the multiparticle level and slitless strategies that have previously been applied in the fields of bioimaging and astrophysics. In MPS (Figure a), QDs are sparsely distributed on a glass substrate and excited by wide-field illumination. Without the use of an entrance slit, the emission from these QDs is directed to our spectrometer that is equipped with a reflective diffraction grating.…”
Section: Resultsmentioning
confidence: 99%
“…However, no studies have quantitatively compared these two methods. Martens et al reported a higher emitter density, higher spectral SNR, and better temporal resolution than other sSMLM implementations using a narrow spectral dispersion; however, this may introduce a higher spectral shift error [ 53 ].…”
Section: Quantitative Imaging and Machine-learning-based Analysis Usi...mentioning
confidence: 99%
“…2f). The corresponding value between raw images and their corresponding ground truth was 25.5 (21)(22)(23)(24)(25)(26)(27)(28)(29) dB (mean [CI 95% ]). As expected from these very similar PSNR and from the visual impression, the structural similarity index (SSIM), a perceptual metric used to quantify the difference between the y_pred images and their corresponding ground truth images, was 0.93 (0.90-0.96) (median [IQR]) (Figure 2g).…”
Section: Training the Networkmentioning
confidence: 99%
“…These are limiting srSMLM performance because the final image resolution depends on the accuracy of each individual localization measurement (the higher the number of emitted photons, the better the pointing precision) and on the spatial density of emitters localized in the final image (Nyquist-Shannon sampling theorem). Some recent attempts have been made for improving srSMLM resolution-either by increasing the photon detection efficiency, [11] proposing new brighter fluorophores [22] -or by enabling imaging with higher emitter densities [24,25] -but the improvements remain overall modest.…”
Section: Introductionmentioning
confidence: 99%